Direct digital control of D.C. machines - Von Zwiklitz, Aubrey Paul (Department of Electrical Engineering, 2016)
This thesis set out to improve on previous methods of digital control of a three phase fully controlled thyristor bridge, using phase control of the thyristors, and to use this bridge for the purpose of controlling the speed of a separately excited D. C. machine, under the supervision of a small digital computer. Interfacing equipment for this purpose was designed and built. Various methods of speed detection were considered, and a simple digital tachometer designed and built. This tachometer was able to feed a digital number, related to the speed of the machine, to the computer, and was accurate to better than 1%. A direct digital control system was then implemented. The behaviour of the system was first studied under open loop conditions in order to determine the parameters of the system, and to discover any shortcomings in it. The behaviour of the closed loop system was then studied, using z-transform analysis, at sampling rates of from twice to eight times the natural frequency of the machine. Initially, the computer was used as an integral controller. The behaviour of the mathematical model was compared to that of the actual system, and the correlation found to be very good. The control system was then compensated, using compensation routines based on the z-transform analysis, and the behaviour of various compensated systems studied at sampling rates varying from 0,4 to 1 second. Again, the actual system response was found to correspond closely to the designed behaviour. Finally, a dual-machine control system, on a time sharing basis, was implemented, and a degree of interrelation between the speeds of the two machines introduced. The control algorithms developed were able to provide speed control to better than l% accuracy, with a 5% or less overshoot in the step response, a delay of one sampling period but no overshoot in the ramp response, and satisfactory behaviour under load transient conditions. The time, and memory, utilization was such that such algorithms could be extended to the control of several machines, using the single computer, if sufficient input and output facilities were available.